THE MECHANISM OF BASALTIC-ANDESITIC SMALL CALDERA-FORMING ERUPTION AT RAUNG VOLCANO, EAST JAVA, INDONESIA - Sauqi Nur Sabila, Firman
Raung Volcano in East Java is one of the most active stratovolcanoes in Indonesia. Situated within the Ijen Volcanic Complex, which formed during the Quaternary period, Raung Volcano features a caldera measuring 2.2 × 1.7 km with a depth of 500 m. Although relatively small, this caldera is significant for study, particularly in the context of its formation mechanism. This research aims to identify the caldera-forming mechanism through various methodologies, including field data collection, volcanostratigraphic analysis, volcanic reconstruction, physical property studies, component analysis, textural analysis, petrography, and geochemistry. The caldera formation mechanism is modeled deterministically by integrating field and laboratory data to comprehensively describe the eruption process, from magma chamber, conduit, to the characteristics of volcanic products at the surface. Stratigraphic observations indicate that the eruption produced explosive products such as pumice-rich pyroclastic falls and flows, scoria, lithics, and effusive products including basaltic lava flows and lahars, categorized into five eruption phases. Lithic components increased while juvenile components decreased from phase 1 to phase 5. The caldera-forming eruption of Raung Volcano is unique as it occurred at the end of the eruption sequence, specifically in phase 4, after a gradual Plinian phase. Phase 4, representing the climactic stage, saw a significant increase in lithic component abundance, accompanied by an increase in decompression rates, magma ascent triggered by the opening of the phase 3 lava dome, and a sudden drop-in mass discharge rate (MDR), marking the caldera formation during this phase. The caldera formation at Raung Volcano resulted from conduit widening followed by the collapse of the volcanic summit, differing from conventional large-caldera formation theories. Repeated eruptions and high decompression rates destabilized the summit, leading to its collapse and the creation of the caldera. The volcanic products of this climactic phase have a trachyandesite-basaltic composition. The eruption was triggered by basaltic magma injection, as evidenced by a decrease in SiO2 levels, extensive crystal fractionation, and magma-wall rock assimilation, indicated by increased CaO, Sr, Nd, and Eu values, as well as abundant fine sieve textures in plagioclase crystals from phase 4. Volcanic activity at Raung Volcano continues, facilitated by the opening of new magma pathways through the central eruption vent within the caldera. Historical records show that this eruption caused approximately 10000 fatalities, making it one of the most catastrophic events at Raung Volcano.